Effects of prior information on decoding degraded speech: An fMRI study. Issue 1 (30th August 2012) - Clos, Mareike; Langner, Robert; Meyer, Martin; Oechslin, Mathias S.; Zilles, Karl; Eickhoff, Simon B.
<x xml:space="preserve">Abstract</x> Expectations and prior knowledge are thought to support the perceptual analysis of incoming sensory stimuli, as proposed by the predictive‐coding framework. The current fMRI study investigated the effect of prior information on brain activity during the decoding of degraded speech stimuli. When prior information enabled the comprehension of the degraded sentences, the left middle temporal gyrus and the left angular gyrus were activated, highlighting a role of these areas in meaning extraction. In contrast, the activation of the left inferior frontal gyrus (area 44/45) appeared to reflect the search for meaningful information in degraded speech material that could not be decoded because of mismatches with the prior information. Our results show that degraded sentences evoke instantaneously different percepts and activation patterns depending on the type of prior information, in line with prediction‐based accounts of perception. Hum Brain Mapp 35:61–74, 2014. © 2012 Wiley Periodicals, Inc.